CONTROLLING DIET EXPERIENCE OF DIABETIC PATIENTS IN BUKITTINGGI, INDONESIA - Amelia, Dona; Srywahyuni, Ade; Merianti, Liza; Yulia, Mita (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: In 2015, the International Diabetes Federation reported that there were 415 million adults aged 20 to 79 with diabetes. Indonesia is among the 10 countries with the high number of diabetic patients and is ranked 7th in the world with the number of patients reaching 10.2 million. Diabetes management can be done through controlling blood sugar through 4 pillars, namely education, diet, exercise, and medication. However, the current phenomena show that many diabetics have poor dietary control so they fail maintain their blood sugar within its normal limits and are at greater risk for diabetes complications. However, we can still find diabetic patients who are able to improve their diet and control their blood sugar. Therefore, getting information from them, especially related to their experience in controlling their diet, is expected to provide hope and motivation for others. Hence, this study aims to find out and expolore the experience of diabetics with controlled blood sugar and dietMethods: This study uses a qualitative research method with a descriptive phenomenology approach. The selection of participants was carried out by using a purposive sampling technique. The number of participants in this study were 5 and data were processed through Colaizzi method.Result:.There are four themes obtained in this study namely: Self-commitment to discipline and dietary compliance, Fruit as an alternative appetite suppresant, Controlling hunger as a habit, and Channelling hunger to activities. Controlling diet for participants has been succesfully done by created a new habit through controlling their hunger, so that they could keep their commitment dan disclipline for dietary compliance, choosing fruits as alternative suppresant and doing activity for channeling the hunger. Therefore it is important for the nurses to educate the diabetic patients about how to deal with diet issues through controlling a hunger as a habit